Multifocal cutaneous tuberculosis luposa with a 60-year course in a patient with disseminated neoplastic process - Pawłoś, Anna; Reduta, Teresa; Bacharewicz, Joanna; Laudańska, Halina; Chodynicka, Bożena; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Tuberculosis luposa, the most common type of cutaneous tuberculosis, usually develops slowly as a single lesion located on the face. There are only a few case reports describing the onset of skin tuberculosis in the site of BCG vaccination. Objective. Presentation of a case of tuberculosis luposa with unusual course. Case report. We present a rare case of a 71-year-old patient with multiple foci of tuberculosis luposa lasting for 60 years with unusual location and onset in the site of BCG vaccination. In this case very fast development of the last lesion was probably connected with impaired immunity in the course of the progressing neoplastic process. Conclusions . At present the diagnosis of cutaneous tuberculosis may be late due to insufficient knowledge of its clinical picture and lack of awareness of increasing frequency of this disease.